Baicalin ameliorates cigarette smoke-induced airway inflammation in rats by modulating HDAC2/NF-κB/PAI-1 signalling. (October 2021) - Zhang, Hu; Liu, Baojun; Jiang, Shan; Wu, Jin-Feng; Qi, Chun-Hui; Mohammadtursun, Nabijan; Li, Qiuping; Li, Lulu; Zhang, Hongying; Sun, Jing; Dong, Jing-Cheng
Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease distinguished by airway remodelling and progressive inflammation. PAI-1 is an important regulator of fibrosis. Recent studies have shown that PAI-1 seems to be involved in COPD progression. Elevated levels of PAI-1 have been found in the lungs of patients with acute inflammation. PAI-1 has been shown to regulate the levels of proinflammatory cytokines in the lungs, such as tumour necrosis factor (TNF)-α and interleukin (IL)-6, indicating that PAI-1 may play a fundamental role during inflammation. In the present study, we investigated the anti-inflammatory role of baicalin, the main active component of Scutellaria baicalensis, against cigarette smoke (extract) (CS/CSE)-induced airway inflammation in vivo and in vitro . For the in vivo study, SD rats were exposed to CS for 1 h/day, 6 days/week, for 24 weeks and treated with baicalin (40, 80 and 160 mg/kg) or budesonide (0.2 mg/kg). For this study, HBE cells were pretreated with baicalin (10, 20, 40 μM) or dexamethasone (10 −7  M) and then exposed to CSE. We found that baicalin treatment could ameliorate CS-induced airway inflammatory infiltration in rats and decrease PAI-1 expression. The ELISA results showed that baicalin significantly inhibited the levels of TNF-α and IL-1β in CS/CSE-exposed rats and cells. Mechanistic studies showed that baicalin enhanced histone deacetylase 2 (HDAC2) protein expression and inhibited the expression of NF-κB and its downstream target PAI-1, and these effects were reversed by the HDAC2 inhibitor CAY-10683. In conclusion, baicalin ameliorated CS-induced airway inflammation in rats, and these effects were partially attributed to the modulation of HDAC2/NF-κB/PAI-1 signalling.